El trabajo no tradicional como posible campo de ruptura con los habitus de género en mujeres mexicanas - Herrera, Cristina M. (El Colegio de México, 2014)
It is to be presented here the general guidelines of a research project in progress, which constitutes a particular moment in my trajectory as researcher in themes of gender violence, family and public policies. From the previous studies on some policies and programs “with a gender perspective” and on the subjectivity of diverse groups of women that had suffered violence conjugal in México, there was the need to problematize the idea of the social construction (and policies) of the female subject as absolute victim of male domination, and of asking and formulating the question for the social and subjective conditions that would make it possible for women to break up with what Bourdieu called gender habitus , this is to say, those dispositions that because of their character, incarnate and unreflexive, would be responsible that many women, even when they were having “objective” conditions to terminate with violent relations, they opt for not doing it and continue tolerating the violence as something “natural” of conjugal relations. In the face of the evidence of other studies on the improvement in women’s educational levels and their access to paid work does not necessarily translate into meaningful changes in gender relations within the couple and in the family, there emerged a certain concern to explore what happens when the extra-domestic activities of women involve some sort of transgression of the cultural borders that establish a female sub-space and another male. If —as suggested by Bourdieu— the rupture of habitus , even when exceptional, changes in rules are possible to occur that rule a particular field and compel the reflexivity of their actors, it becomes interesting to study the Mexican women’s experience that performed their occupations traditionally considered masculine, and analize their experience an impact on the way in which they comprehend and live the gender relations in the familial and conjugal environments. Here, it is presented the analytic frame and some theoretical-methodological lineaments of this proposal